PENGARUH MENONTON SINETRON ANAK LANGIT TERHADAP PERILAKU MENIRU ADEGAN KEKERASAN DIKALANGAN ANAK USIA 12-17 TAHUN DI JAGALAN RW 13 JEBRES SURAKARTA - Andari, Retno; Buddy Riyanto, Maya Sekar Wangi, (Solidaritas, 2017)
PENGARUH MENONTON SINETRON ANAK LANGIT TERHADAP PERILAKU MENIRU ADEGAN KEKERASAN DIKALANGAN ANAK USIA 12-17 TAHUN DI JAGALAN RW 13 JEBRES SURAKARTAOleh Retno Andari1, Dra. Maya Sekar Wangi, M,Si2 , Drs. Buddy Riyanto, M.Si3ABSTRACT Television is a mass media of communication that has a composition of audio and visual, which people are able to see through audio and visual viewing. The purpose of this research is to prove the effect of watching Sinetron Anak Langit in the behavior of imitating violent scenes among children 12-17 years old in Jagalan RW13 village. This research used quantitative method with explanatory research type. Data obtained using questionnaire then tested with product moment analysis, simple regression, coefficient of determination, residual test, and t-test. The sample of this research is children of 12-17 years old in Jagalan RW 13, Jagalan Village, Jebres sub-district, Surakarta with amount 85 children by total sampling technique. The hypothesis of this study is able to accept by the truth, it is proven by product moment analysis value of 0.703. The value of this correlation is positive which means that higher the level of watching Sinetron Anak Langit, behavior of imitating the scene of violence is also higher. Key words: Watching Sinetron, Mimic Behavior, Violence